ASSESSMENT OF PLANT DIVERSITY INDICES OF GOMATI RIPARIAN CORRIDORS IN DISTRICT JAUNPUR, INDIA - Singh, Mayank; Singh, M. P. (Ecoprint: An International Journal of Ecology, 2014)
Riparian ecosystems, the central elements in many landscapes, are described as an ecotone stretchedout across the landscape because of their shape diversity and function as filters and corridors still theyare most disturbed and threatened by humans. The present work deals with seasonal dynamics inplant diversity indices at two distinct sites (I and II) at ecotonal belts of River Gomati, Jaunpur (U.P.).The diversity indices of plant community have been computed on the basis of density values recordedfrom April, 2012 to March, 2013. Site I showed more species richness and evenness as compared tosite II. Shannon and Weaver, Evenness, Marglef’s, McIntosh and Menhinic diversity indices valueswere higher at site I compared to site II. In contrast, the concentration dominance showed highervalue at site II, whereas Simpson values of diversity have fluctuated in different seasons at both thesites (I and II). It finally deals to formulate strategies and methods for the management of plantdiversity and other natural resources based on various ecological studies, and logical grounds. DOI: http://dx.doi.org/10.3126/eco.v20i0.11444 ECOPRINT An International Journal of Ecology Vol. 20, 2013 Page: 71-76